Spatio-temporal Evolution of Urban Economic Resilience in Henan Province - Peng, Jingxiao; Zhai, Jiumei (International Journal of Global Economics and Management, 2024)
With the progress of The Times and the slogan of the risk of the Central Plains getting cloud and cloud, the cities of Henan province have made progress and development to varying degrees in terms of economy, culture, science, and technology However, the development of the cities of Henan Province still needs our attention Through the city’s economic resilience city in Henan province was studied by the comparative analysis of the difference of economic resilience, using the data from 2007-2020 by entropy method and spatial autocorrelation method to the analysis of the time and space, to explore the city of Henan province space time evolution process and law of economic resilience, then we can understand the economic resilience. The evolution situation of Henan province of the central plains, the results are as follows: (1) The resistance of urban economy in Henan province shows a stable trend over time and is most not affected by COVID-19 (2) Spatially, the economic resistance of cities in Henan province is concentrated The economic resistance of the cities is generally higher in the north than in the south, and the economic resistance of the cities in the west is generally higher than that of the cities in the east On the whole, the economic resilience of the cities is concentrated in the central cities (3) Economic innovation capacity, including R&D expenditure, technology market turnover and the number of students in colleges and universities, the ratio of actual utilized foreign capital to GDP has a great impact on economic resilience In the future development process, more rational use of foreign capital and the improvement of innovative economic system are needed.